Two-dimensional lateral heterojunction through bandgap engineering of MoS2 via oxygen plasma. (8th July 2016) - Choudhary, Nitin; Islam, Muhammad R; Kang, Narae; Tetard, Laurene; Jung, Yeonwoong; Khondaker, Saiful I
Abstract: The present study explores the structural, optical (photoluminescence (PL)), and electrical properties of lateral heterojunctions fabricated by selective exposure of mechanically exfoliated few layer two-dimensional (2D) molybdenum disulfide (MoS2 ) flakes under oxygen (O2 )-plasma. Raman spectra of the plasma exposed MoS2 flakes show a significant loss in the structural quality due to lattice distortion and creation of oxygen-containing domains in comparison to the pristine part of the same flake. The PL mapping evidences the complete quenching of peak A and B consistent with a change in the exciton states of MoS2 after the plasma treatment, indicating a significant change in its band gap properties. The electrical transport measurements performed across the pristine and the plasma-exposed MoS2 flake exhibit a gate tunable current rectification behavior with a rectification ratio up to 1.3 × 10 3 due to the band-offset at the pristine and plasma-exposed MoS2 interface. Our Raman, PL, and electrical transport data confirm the formation of an excellent lateral heterojunction in 2D MoS2 through its bandgap modulation via oxygen plasma.